EVALUASI KINERJA JARINGAN SYARAF TIRUAN PADA PERAMALAN KONSUMSI LISTRIK KELOMPOK TARIF RUMAH TANGGA - I Putu Eka N. Kencana; Ketut Jayanegara (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2012)
Many methods have been applied in forecasting technics, varied fromStatistical Forecasting Methods (SFM) or Mathematical Modelling and ForecastingMethods (MMFM) to Artificial Neural Methods (ANM). This research aimedto implement and evaluate performance of Artificial Neural Network (ANN), onemethod in ANM group; for forecasting electricity consumption by household inProvince of Bali. This research used electricity consumption data from January2001 to December 2009 as basis for network’s training and validating its result.The actual data from January to December 2010 is used to evaluate the performanceof network prediction. Research shows the Mean Absolute Prediction Error(MAPE) of the ANN’s prediction is 7,56%.